Insights Into the Role of Mitochondrial Ion Channels in Inflammatory Response - Ponnalagu, Devasena; Singh, Harpreet (Frontiers in Physiology, 2020)
Mitochondria are the source of many pro-inflammatory signals that cause the activation of the immune system and generate inflammatory responses. They are also potential targets of the pro-inflammatory mediators, thus triggering a severe inflammatory response cycle. As mitochondria is a central hub in immune system activation, their dysfunction leads to many inflammatory disorders. Thus, strategies aiming at regulating mitochondrial dysfunction can be utilized as a therapeutic tool to cure inflammatory disorders. Two key factors that determine the structural and functional integrity of mitochondria are mitochondrial ion channels and transporters. They are not only important for maintaining the ionic homeostasis of the cell, but also play a role in regulating reactive oxygen species generation, ATP production, calcium homeostasis and apoptosis, which are common pro-inflammatory signals. The significance of the mitochondrial ion channels in inflammatory response is still not clearly understood and will need further investigation. In this article, we review the different mechanisms by which mitochondria can generate the inflammatory response as well as highlight how mitochondrial ion channels modulate these mechanisms and impact the inflammatory processes.